Clinical and laboratory assessment of mineral deficiencies in grazing sheep and goats at Sana’a Governorate, Yemen (Yemeni Journal of Agriculture & Veterinary Sciences, 2025)
Mineral deficiency represents a major health challenge affecting the productivity of small ruminants. This study aimed to evaluate mineral deficiencies in grazing sheep and goats at Sana’a Governorate, Yemen, and their association with hematological and biochemical parameters. A total of 200 local sheep (n=100) and goats (n=100), aged 1–4 years and maintained exclusively on pasture grazing were selected and investigated. Among these, 160 animals (80 sheep and 80 goats) showed signs of mineral deficiencies and considered as affected animals or deficient animals; while, 40 animals (20 sheep and 20 goats) appeared healthy and considered as controls. The clinical examination revealed, In deficient animals, the following clinical signs: easily detached and discolored hair or wool, alopecia, pale mucous membranes, inappetence, emaciation, and lethargy, with significantly elevated (P<0.05) pulse and respiratory rates. Hematological analysis revealed significantly decrease (P<0.05) of Hb, PCV, RBC, and WBC counts accompanied by increase of RDW and platelet counts. Biochemical evaluation demonstrated significantly decrease (P<0.05) levels of Ca, P, Mg, Cu, Fe, Zn, total protein, and albumin in deficient animals compared to controls. The study concluded that naturally grazed sheep in different Sana`a localities, exhibited variable degrees of clinical signs and serum minerals deficiency that led marked deceases in performance and health of animals. Hence, mineral supplementation in the form of mineral mixture or other preparations of these animals is recommended. Further studies are also encouraged to explore long-term impacts of mineral supplementation on health, productivity, and reproductive performance in small ruminants in study areas.